Evaluation of Shorting Facility Toward Archived Sustainable Waste Recovery in Talang Gulo landfill, Jambi City - Andra Puput Marya Ani; Mega Muitiara Sari; Iva Yenis Septiariva; I Wayan Koko Suryawan (METANA, 2022)
Talang Gulo landfill has now been converted into a sanitary landfill system. In the management system, the incoming waste is sorted first. The purpose of this study was to evaluate the process of shorting waste at the Talang Gulo landfill to reduce the waste generation that is the reduction in landfills. This research was conducted by direct observation and using secondary data. The decrease in the number of waste reductions in Jambi City from 2019 to 2020 (9.52% to 1.77%). Data collection during June 2021 shows that the average generation that goes into landfills is 312.44 kg/day. The amount of waste that can be recovered from the shorting process is 2.4% of the total that goes to the shorting facility. The types of waste that are shorted consist of polyethene terephthalate (PET), high-density polyethene (HDPE), polypropylene (PP), low-density polyethene (LDPE), aluminium, and glass. Where in the shorting process consists of two types of processes, namely mechanical and manual. The shorting with the mechanical and manual process obtained the highest PET waste with values, 38.82% and 56.8% respectively. The composition of the recovered waste in the Talang Gulo TPA Shorting Area is as follows LDPE Plastic 10.20%; aluminium 5.21%; Glass 1.30%; PET Plastic 38.83%; HDPE Plastic 24.3% and PP Plastic 20.17%.